Cutting Tool Performance in End Milling of Glass Fiber-Reinforced Polymer Composites - Bilek, Ondrej; Zaludek, Milan; Cop, Jiri (Manufacturing Technology Journal, 2016)
The article deals with the machining of glass fiber-reinforced thermoset composite. Emphasis is placed on the selection of cutting tools for end milling. Experiment involved slot milling by special tools for composite machining with different geometries and surface coating. Further, the quality of the machined surface, cutting performance, dimensional accuracy, delamination factor and tool wear were evaluated. The results were compared with the end milling of carbon fiber-reinforced polymer composites.
Keywords: End Milling; GFRP; CFRP; Composites; Cutting Tools